Islamic Banking Development In BIMP-EAGA Countries: Issues And Potential Cooperation - Amin, H.; Muhammad, M. Z.; Lada, S.; Amran, A.; Abdul Hamid, M. R.E (Universiti Sains Islam Malaysia, 2024)
This study analyses the Islamic banking system development in BIMP-EAGA countries since 1983. An analytical method of comparative study is employed for Brunei, Indonesia, Malaysia and Indonesia to verify the discrepancy of the countries in terms of Islamic banks. In Bruei, the evidence suggests that Sultan Haji Hassanah Bolkiah Mu'izzaddin Waddaulah is committed to inease the number of Islamic banks since 1990s. The evidence from Indonesia suggests that the development of Islamic banks has showed significant progress due to long term plannig by Bank Indonesia (BI) to increase Islamic bank role at national economy. Similarly, the evidence from Malaysia sugqests that Islamic banking development involves an active systematic growth due to the commitment from the government. Unlike in Philippines, Islamic banking system is underperformed due to the passive programs carried by the goverment unlikely to construct it as a national policy. Positive reforms by creating a number of assistances between countries may possible to minimize those gaps.